Politeness Strategies Used by the Main Characters in Christopher Robin (2018) Film - Rachman, Khairur; Arifin, M. Bahri; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
This research focuses on the politeness strategies used by the main characters of Christopher Robin film. The objectives of this research are to find out the politeness strategies used by the main characters of the film and to explain the motivations of the main characters of the film in using the politeness strategies. This research is a qualitative research with content analysis approach. The data sources of this research are the screenplay of Christopher Robin film and the transcript of the dialogue done in the film. The data were taken from the dialogues and utterances from the main characters containing politeness strategies. All of the main characters of the film used politeness strategies. However, not all of the main characters used all of the types of politeness strategies. Christopher was the one who used the politeness strategies most because he was the character who had the utterances and dialogues most compared with the other main characters. Pooh, as the second main character, did not use any off record strategy to all other characters he interacted with. The last main character, Madeline, used the off record politeness strategy most, in contrast with Pooh, even with the fact that she had the least dialogues from all of the main characters. For the motivation in using politeness strategies, only Christopher had the two kinds of motivation in using politeness strategies: intrinsic payoffs and sociological variables circumstances; Pooh and Madeline only had one of those kinds: intrinsic payoffs.